2021
DOI: 10.3389/fped.2021.643299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coronavirus Disease 2019 (COVID-19) on Peripheral Blood Lymphocytes and Their Subsets in Children: Imbalanced CD4+/CD8+ T Cell Ratio and Disease Severity

Abstract: Introduction: While pathogenesis in COVID-19 is not fully known and the effects between SARS-CoV-2 and the immune system are complicated, it is known that lymphopenia, hyper-inflammatory responses, and cytokines play an important role in the pathology of COVID-19. While some hematological abnormalities have been described among the laboratory features of COVID-19, there have not been studies reported on lymphocyte subset analyses in children. The aim of this study was to describe lymphocyte subsets in pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…Such pathology is mainly observed in HIV and correlates with an advancement of the disease. Still, in COVID-19 patients a significance of this finding is unclear [ 25 ]. On the contrary, Argun et al did not find any differences neither in total lymphocyte count nor in CD4 + /CD8 + index between mild/asymptomatic COVID-19 pediatric patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Such pathology is mainly observed in HIV and correlates with an advancement of the disease. Still, in COVID-19 patients a significance of this finding is unclear [ 25 ]. On the contrary, Argun et al did not find any differences neither in total lymphocyte count nor in CD4 + /CD8 + index between mild/asymptomatic COVID-19 pediatric patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have also assessed lymphocyte subsets in immunocompetent children with COVID-19. They proved that children, unlike adults, rarely have lymphopenia in the course of SARS-CoV-2 infections, and if present, its degree correlates with the severity of the disease and usually affects all lymphocyte subsets [ 16 ]. Our study did not reveal a tendency for lymphopenia in children, regardless of the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…14 Various studies demonstrated T lymphocyte abnormalities in COVID-19 infection and as in other viral infections these alterations may be responsible for the relapses of nephrotic syndrome. 15 Except for multisystem inflammatory syndrome, the most remarkable feature of COVID-19 is the lower risk of severe forms of disease in children when compared with adult counterparts. But even asymptomatic disease course may be responsible for relapses in nephrotic syndrome patients as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%